The Impact of International Support on the Iraqi Military Institution after the American Occupation of Iraq (2003-2018) - Judeh Sabih AL-Maliki , Prof. Assist .Dr. Ali (Basra studies journal, 2024)
This study aims to explore the reasons and factors that motivated the United States of America to occupy Iraq, assess the resulting military, social, and economic conditions, and examine the various problems and disturbances that ensued. It also identifies the most significant decisions made by the American occupation authority, including the dissolution of the Iraqi military institution, which led to a security and military vacuum. Consequently, a decision was made to rebuild the Iraqi army and the broader General Military Institution. This research emphasizes the role and impact of international support on the General Military Institution, highlighting how it contributed to overcoming the terrorist organization ISIS, modernizing the military, and fostering development despite the challenges and negative repercussions that remained.